SCIENCE AS A COMPONENT OF THE HIGHER EDUCATION SYSTEM - Elena V. Sen’Ko (Высшее образование в России)
The article deals with the main objectives of research work in higher educational institutions. Analyzing its traditional virtual indicators and those that were recently activated, the author states the multidimensional nature of research activity at the present stage of development of higher education. In this analytical context science is studied as a required element in the system of training specialists with higher education; in accordance with the requirement of the day the universities should be both educational and scientific institutions. The author argues that the purpose of philological education cannot be reduced to methodical training of a school teacher, because the important product of this education is the research and innovation intellectual environment. It plays an important role in the training of modern professionals, which are able not only to reproduce and to share with their knowledge, but also to understand the relevant scientific paradigms, to think creatively and generate their own scientific ideas and ways to realize them.